Seasonal variation of morphological traits, wood formation, and soil properties differs betweenQuercus roburL. andRobinia pseudoacaciaL. saplings - Özden Keleş, Seray; Savaci, Gamze (Informa UK Limited, 2021)
Climate seasonality is one of the important environmental variables that can drive changes in many properties of trees. However, how different tree species regulate their growth and development dur...
Keywords: 15. Life on land